Morphometric study of the blood supply of pedunculated colon polyps: What is the optimal position on the stalk for snare resection? - Noriyuki Isohata; Daiki Nemoto; Kenichi Utano; Shungo Endo; Gaku Tanaka; David G. Hewett; Kazutomo Togashi (Endoscopy International Open, 2015)
Background and study aims: Bleeding after colonoscopic resection of pedunculated polyps cannot be easily predicted. The aims of this study were to evaluate the blood supply in pedunculated polyps and to clarify the optimal position on the polyp stalk for snare placement to prevent post-polypectomy hemorrhage. ]Patients and methods: In one institution, 11 pedunculated polyps from 11 patients were studied prospectively. All polyps were resected at the base of the stalk using a snare wire with electrocautery. Histologic axial sections from the apex and base of the stalk were examined with hematoxylin eosin and elastica stains. Elastica stains were used to identify blood vessels. The cross-sectional area of the stalk, total vessel area, maximum diameter of artery/arteriole lumen, number of thick (≥ 0.1 mm) vessels, and number of arteries/arterioles were measured in each section with image processing software. Wilcoxon signed-ranks test was used for comparison. Results: The median polyp diameter was 16 mm (range 7 to 24 mm) and median length of the stalk was 11 mm (range 7 to 23 mm). Two invasive cancers (T1) were included. The maximum diameter of the arterial/arteriolar lumen was greater at the base (P = 0.0044), whereas the ratio of the vessel area to the cross-section area was greater at the apex (P = 0.016). The number of thick vessels and arteries/arterioles were equivalent between apex and base. Conclusions: Morphometric study of the blood supply of pedunculated polyps confirmed that the optimal site for the excision of pedunculated polyps is in the middle of the stalk.